Ion Channel Expression and Characterization in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Zhihan Zhao; Huan Lan; Ibrahim El-Battrawy; Xin Li; Fanis Buljubasic; Katherine Sattler; Gökhan Yücel; Siegfried Lang; Malte Tiburcy; Wolfram-Hubertus Zimmermann; Lukas Cyganek; Jochen Utikal; et al. (Stem Cells International)
Background. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are providing new possibilities for the biological study, cell therapies, and drug discovery. However, the ion channel expression and functions as well as regulations in hiPSC-CMs still need to be fully characterized. Methods. Cardiomyocytes were derived from hiPS cells that were generated from two healthy donors. qPCR and patch clamp techniques were used for the study. Results. In addition to the reported ion channels, INa, ICa-L, ICa-T, If, INCX, IK1, Ito, IKr, IKs IKATP, IK-pH, ISK1–3, and ISK4, we detected both the expression and currents of ACh-activated (KACh) and Na+-activated (KNa) K+, volume-regulated and calcium-activated (Cl-Ca) Cl−, and TRPV channels. All the detected ion currents except IK1, IKACh, ISK, IKNa, and TRPV1 currents contribute to AP duration. Isoprenaline increased ICa-L, If, and IKs but reduced INa and INCX, without an effect on Ito, IK1, ISK1–3, IKATP, IKr, ISK4, IKNa, ICl-Ca, and ITRPV1. Carbachol alone showed no effect on the tested ion channel currents. Conclusion. Our data demonstrate that most ion channels, which are present in healthy or diseased cardiomyocytes, exist in hiPSC-CMs. Some of them contribute to action potential performance and are regulated by adrenergic stimulation.